PENDIDIKAN KARAKTER PERSPEKTIF ISLAM (Studi Pemikiran KH. Abdul Wahid Hasyim) - Nindia Puspitasari (Universitas Muhammadiyah Metro, 2017)
This research is motivated by the importance of character education in Indonesia an Islamic perspective. Some things are a matter of concern is the declining values of character, it is marked by moral degradation of youth, ranging from fighting between students, drugs, violence, murder and others. Various attempts were made to address the moral decadence of the young generation, among whom was the launching of character education in environmental education, both formal and non-formal. This study is a literature study or (library research) by making the life history K.H Abdul Wahid Hashim and some works tulisanya as research objects. This study uses data collection techniques documentation. After doing research on the life history K.H Abdul Wahid Hasyim and some of his papers, produced two findings. First, there are twelve values of character education that seeks implanted K.H Abdul Wahid Hasyim. Twelve of these values are; religious values, the values of tolerance, the value of discipline, values of hard work, the value of an independent, democratic values, creative values, the value of the national spirit, the value of patriotism, the value of friends / communicative, fond of reading and the value of curiosity value. While both findings in this study, explained that the values of character education K.H Abdul Wahid Hasyim in line with the goal of character education. He sought to build a national life of a multicultural, build a civilization of intelligent, cultured noble, and capable of contributing to the development of human life, developing the potential of the base in order to be good, good thoughts, and behave well and exemplary good, to build a sense of citizenship that loves peace, creative, independent, and able to coexist with other nations in a harmony.Keyword: Character Education, KH. Abdul Wahid Hasyim’s Thought